Liberty's torch the great adventure to build the Statue of Liberty - Mitchell, Elizabeth (Atlantic Monthly Press, 2014)
The Statue of Liberty has become one of the most recognizable monuments in the world: a symbol of freedom and the American Dream. But the story of the creation of the statue has been obscured by myth. In reality, it was the inspiration of one quixotic French sculptor hungry for fame and adoration: Frederic Auguste Bartholdi. Bartholdi showed himself to be a talented sculptor at the tender age of twenty-one when a statue he created won third prize at the 1855 Paris Exhibition. His equally prodigious talent for entrepreneurship came to light soon afterwards. Following a trip to Egypt where he was inspired by the pyramids and the Sphinx, and with France in turmoil following the Franco-Prussian war, Bartholdi made for America, carrying with him the idea of a colossal statue of a woman in his mind. With no help coming from the French and American governments, he enlisted the help of a number of notable men and women of the age, including Joseph Pulitzer, Victor Hugo, Gustave Eiffel, and Emma Lazarus, and through a variety of money-making schemes and some very modern-seeming fundraising campaigns, collected almost all of the money required to build the statue himself